Reproduction of Megapitaria squalida (Bivalvia: Veneridae) in the Southeast Gulf of California, Mexico - Álvarez-Dagnino, Ernesto (2017)
Bivalves reproductive cycle varies according to the particular environmental conditions where they are found, and these reproductive details represent basic information for their capture, management and conservation strategies. With this objective, the reproductive cycle of the clam Megapitaria squalida, inhabiting the Southeast of the Gulf of California (Altata Bay, Sinaloa, Mexico), was studied using histology and changes in the number and size of oocytes, from June 2013 to June 2014. Histological analysis of the gonads showed spawning activity throughout the year, with two peaks. The first was registered in October and it was accompanied by the highest decrease of weight; the second was in February with the highest percentage of spawning population; besides, a resting period was observed in December. The sex-ratio (female:male) of the clam population was 1.08:1 (χ2 = 5.72, d.f. = 1, P < 0.05). Mean oocyte size and number were different (P < 0.05) among all sampling months and fluctuated from 34.6 ± 5.8 µm in June 2014, to 41.9 ± 6.8 µm in February 2014, and from 443.8 ± 424.5 in February 2014, to 1 214.4 ± 267.6 counted in April, respectively. With these results we suggest a protection season from October to November, when the most intense release of gametes occur in this population.